2015
DOI: 10.1103/physrevb.91.054301
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen vacancy, self-interstitial diffusion, and Frenkel-pair formation/dissociation inB1TiN studied byab initioand classical molecular dynamics with optimized potentials

Abstract: We use ab initio and classical molecular dynamics (AIMD and CMD) based on the modified embedded-atom method (MEAM) potential to simulate diffusion of N vacancy and N self-interstitial point defects in B1 TiN. TiN MEAM parameters are optimized to obtain CMD nitrogen point-defect jump rates in agreement with AIMD predictions, as well as an excellent description of TiN x (∼0.7 < x 1) elastic, thermal, and structural properties. We determine N dilute-point-defect diffusion pathways, activation energies, attempt fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 92 publications
5
46
0
1
Order By: Relevance
“…7. These are approximately one order of magnitude smaller than N vacancy migration rates, obtained from classical molecular dynamics simulations [54], at all investigated temperatures (see Fig. 7 and Table II Table II is due to lattice vibrations.…”
Section: B Ti Vacancy Equilibrium Jump Ratesmentioning
confidence: 94%
See 2 more Smart Citations
“…7. These are approximately one order of magnitude smaller than N vacancy migration rates, obtained from classical molecular dynamics simulations [54], at all investigated temperatures (see Fig. 7 and Table II Table II is due to lattice vibrations.…”
Section: B Ti Vacancy Equilibrium Jump Ratesmentioning
confidence: 94%
“…Recent classical and ab initio molecular dynamics simulations of N point-defect diffusion in bulk TiN demonstrated that N monovacancy migration is the primary mechanism for transport of N atoms [54]. Our present theoretical investigations focus on migration of Ti monovacancies at the dilute limit, as this is expected to be the most important reaction pathway for diffusion of metal atoms in overstoichiometric (TM/N ratio < 1) bulk TiN.…”
Section: Computational Details and Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that anion surface vacancies are highly stable, as expected for all TM nitrides; strong TM-N bonds hinder N diffusion. 63,121 Due to the use of periodic boundary conditions, desorbed Nad/Nsurf molecules rebound from the bottom layer of the overlying slab replica to return to the upper layer of the slab from which they desorbed. AIMD simulations show that the presence of N vacancies catalyzes N2 molecular dissociation on VN(001), as observed previously for TiN(001).…”
Section: N-vacancy Surface Migration and Vacancy-catalyzed N2 Dissocimentioning
confidence: 99%
“…62,63 Very few theoretical studies have considered the interaction of TM nitride surfaces with gases and metal adatoms via ab initio molecular dynamics (AIMD). 64,65 Recently, we investigated mass transport of Ti and N adatoms, together with TiNx (x = 1-3) admolecules, on TiN(001) [62,[66][67][68][69] and TiN (111) [70] surfaces, and bulk diffusion in TiN, 63 by both ab initio and classical molecular dynamics. MD simulations show that isolated N adatoms (Nad) on TiN(001) favor threefold sites (TFS) near, and strongly bonded with, nitrogen surface atoms (Nsurf) and bounded by two Ti surface atoms.…”
Section: Introductionmentioning
confidence: 99%